ISSUES OF FINANCIAL SECTOR DEVELOPMENT IN THE CENTRAL ASIAN COUNTRIES (American Journal of Interdisciplinary Research and Development, 2023)
This article is devoted to the consideration of the issues related to the development of the financial sector in Central Asian countries as a factor of sustainable development. In addition, the article analyzes the areas of banking system reforms in the countries of the region, the process of structural changes in the economy made through investments, problems with the improvement of the investment environment.